Approach to Efficiency of the Low Frequency Inductive Heating of Ferromagnetics - Miedzinski, B.; Okraszewski, Z.; Wang, X.; Xu, Lj. (Elektronika ir Elektrotechnika, 2008)
The heating system using a low frequency supply has been used for heating long ferromagnetic elements. The theoretical considerations using ANSYS program were performed for 2D distributions of the both temperature and magnetic field over the rail cross section. Transversal magnetic field was analyzed for different frequency as well as various MMF of the power source applied. The influence of the heater location and cooling intensity of the environment was taking into account. The calculation results create a basis for further three dimensional considerations allowing for selection of the heating strategy. Ill. 10, bibl. 3 (in English; summaries in English, Russian and Lithuanian).